LNSS Project - Erasmus +: achievements and impact (Confluenţe Bibliologice, 2016)
In this article the author presents the International Project applied  in BS USARB: LNSS-Erasmus+. She oﬀers reﬂacting of the goals, objectives and creation of the working  project team. All kinds of activities and trainings are presented inside the project.
Keywords: Information Literacy; LNSS project